IMPLEMENTATION OF BUILDING INFORMATION MODELLING (BIM) FOR ROAD INFRASTRUCTURE IN THE DESIGN PHASE - Sulistyowati Sulistyowati; Iryan Dwi Handayani (Universitas Semarang, 2023)
The implementation of BIM has long been known to building but is still relatively new to road infrastructure. With various demands such as safety, comfort and maintenance budget, the traditional way of managing road infrastructure is considered inadequate. According to UNECE (United Nation Economic Commission for Europe), in large-scale of infrastructure project, more than 50 percent of contract modification - which is considered inefficient - are related to deficiencies, BIM provides an effective way to overcome this by integrating all the stakeholder since the design phase to post construction phase. This article reviews the implementation of Building Information Modelling (BIM) in road infrastructure, particularly in the design phase. The methodology used is by reviewing some journals discussing implementation of BIM in road infrastructure.